Epistasis between the DAT 3' UTR VNTR and the COMT Val158Met SNP on cortical function in healthy subjects and patients with schizophrenia - Prata, Diana P; Mechelli, Andrea; Fu, Cynthia H.Y; Picchioni, Marco; Toulopoulou, Timothea; Bramon, Elvira; Walshe, Muriel; Murray, Robin M; Collier, David A; McGuire, Philip (Proceedings of the National Academy of Sciences - PNAS, 2009)
Dopamine has a crucial role in the modulation of neurocognitive function, and synaptic dopamine activity is normally regulated by the dopamine transporter (DAT) and catechol-O-methyltransferase (COMT). Perturbed dopamine function is a key pathophysiological feature of schizophrenia. Our objectives were (i) to examine epistasis between the DAT 3' UTR variable number of tandem repeats (VNTR) and COMT Val158Met polymorphisms on brain activation during executive function, and (ii) to then determine the extent to which such interaction is altered in schizophrenia. Regional brain response was measured by using blood-oxygen-level-dependent fMRI during an overt verbal fluency task in 85 subjects (44 healthy volunteers and 41 patients with DSM-IV schizophrenia), and inferences were estimated by using an ANOVA in SPM5. There was a significant COMT x DAT nonadditive interaction effect on activation in the left supramarginal gyrus, irrespective of diagnostic group (Z-score = 4.3; family-wise error (FWE) p = 0.03), and in healthy volunteers alone (Z-score = 4.7; FWEp = 0.006). In this region, relatively increased activation was detected only when COMT Met-158/Met-158 subjects also carried the 9-repeat DAT allele, or when, reversely, Val-158/Val-158 subjects carried the 10/10-repeat genotype. Also, there was a significant diagnosis x COMT x DAT nonadditive interaction in the right orbital gyrus (Z-score = 4.3; FWEp = 0.04), where, only within patients, greater activation was only associated with a 9-repeat allele and Val-158 conjunction, and with a 10-repeat and Met-158 conjunction (Z-score = 4.3; FWE p = 0.04). These data demonstrate that COMT and DAT genes interact nonadditively to modulate cortical function during executive processing, and also, that this effect is significantly altered in schizophrenia, which may reflect abnormal dopamine function in the disorder.